2020
DOI: 10.3390/ijerph17249373
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Solutions Reducing Soil and Groundwater Contamination from Fertilizers in Arid and Semi-Arid Regions: Case Study the Eastern Nile Delta, Egypt

Abstract: Intensive agriculture requires increasing application of fertilizers in order to sustain food production. Improper use of these substances in combination with increasing seawater intrusion results in long-term and nonpoint soil and groundwater contamination. In this work, a 3-D groundwater and solute transport numerical model was created to simulate the effect of excessive fertilizers application along the Bahr El Baqar drain system, in the eastern Nile Delta, Egypt. The geotechnical properties of the soils, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 28 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…The results are consistent with Abd-Elhamid et al [ 19 ] who approved that increasing pumping rates led to increase the aquifer contamination. Additionally, Figure 11 shows the increasing of the wastewater recharge rates ( R ) to 401.5, 438, 474.5, 511, and 547.5 mm/year compare with 365 mm/year at base case led to increase the COD distribution in aquifer to 52.73, 56.02, 59.29, 62.8, and 65.65 ppm at a depth of 25 m and 22.27, 24.6, 27.53, 30.73, and 32.7 ppm at a depth of 50 m. These findings according to Abd-Elaty et al [ 21 ] who studied the effect of increasing fertilizers concentration and combination of pumping rates with fertilizer rates led to increase aquifer contamination. Applying different pumping rates with increasing wastewater recharge rates as in the combination case increased COD in groundwater to 56.60, 65.53, 72.55, 79.48, and 85.70 ppm at a depth of 25 m and reached 24.79, 30.59, 36.51, 44.54, and 56.06 ppm at a depth of 50 m as shown in Figure 11 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The results are consistent with Abd-Elhamid et al [ 19 ] who approved that increasing pumping rates led to increase the aquifer contamination. Additionally, Figure 11 shows the increasing of the wastewater recharge rates ( R ) to 401.5, 438, 474.5, 511, and 547.5 mm/year compare with 365 mm/year at base case led to increase the COD distribution in aquifer to 52.73, 56.02, 59.29, 62.8, and 65.65 ppm at a depth of 25 m and 22.27, 24.6, 27.53, 30.73, and 32.7 ppm at a depth of 50 m. These findings according to Abd-Elaty et al [ 21 ] who studied the effect of increasing fertilizers concentration and combination of pumping rates with fertilizer rates led to increase aquifer contamination. Applying different pumping rates with increasing wastewater recharge rates as in the combination case increased COD in groundwater to 56.60, 65.53, 72.55, 79.48, and 85.70 ppm at a depth of 25 m and reached 24.79, 30.59, 36.51, 44.54, and 56.06 ppm at a depth of 50 m as shown in Figure 11 .…”
Section: Discussionmentioning
confidence: 60%
“…This results in a lack of direct discharge, and supply of nutrients to water bodies [ 20 ]. Abd-Elaty et al [ 21 ] carried out geotechnical and numerical study for applied solutions to reduce soil and groundwater contamination by fertilizers in arid and semi-arid regions in the Eastern Nile Delta, Egypt. The result showed that silty clay soils are able to contain the contaminations and preserve the groundwater quality, and, more than pumping, has a positive effect for groundwater contamination and negative effect for soil pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The Eastern Nile Delta Aquifer (ENDA) is located between latitudes 30 • 00 , 31 • 30 north and longitudes 31 • 00 , 32 • 30 east with a total area of 14,000 km 2 . The ENDA has a predominantly agricultural nature with a high density of overlapping irrigation and drainage networks which follow from the south to the north, as shown in Figure 1 [21,26]. The area is bounded by the Damietta branch in the west, Suez Canal in the east, El Manzala Lake in the north, and Ismailia canal in the south.…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…The hydraulic conductivity of sand-bentonite mixtures (80% sand and 20% bentonite) has been tested and calculated to be 0.033 m/d [19]. Different numerical simulations have been applied to study protecting groundwater from polluted streams using lining, a cutoff wall, and increasing fresh groundwater [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that lowering the conductivities of liner materials lowered the contaminates spread. In the eastern Nile Delta of Egypt, Abd-Elaty et al ( 2020 ) created simulation-based methods to reduce soil and groundwater contamination from fertilizers; the results revealed that installing a drainage network reduces groundwater and soil contamination.…”
Section: Introductionmentioning
confidence: 99%